A kind of iron-based amorphous alloy magnetic powder, composite microwave absorbing coating prepared therefrom and preparation method thereof
By mixing the iron-based amorphous alloy magnetic powder with the ferrosilicon aluminum alloy powder in a certain proportion, the composite absorbing coating was prepared, which solved the problems of poor economicality and impedance mismatch of existing Fe-based amorphous absorbing materials, and realized the absorbing materials with excellent high-frequency wave absorption performance and good economicality.
Patent Information
- Application Number
- CN202510054460.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
AI Technical Summary
The existing Fe-based amorphous absorbing materials require the use of expensive metal elements such as Nb and W, which leads to poor economic and industrial practicality, and the impedance of the traditional ferrosilicon aluminum alloy absorbing coating does not match, deteriorating the absorbing effect.
The iron-based amorphous alloy magnetic powder is used, and its chemical composition is: silicon content 5 at.%, boron content 7.5 at.%, phosphorus content 7 to 9 at.%, carbon content 2 at.%, chromium content 2 at.%, and the balance is iron. Ultrafine sheet iron-based amorphous alloy magnetic powder is prepared by water and gas combined atomization method, and mixed with the ferrosilicon aluminum alloy powder in a certain proportion to prepare a composite absorbing coating.
It realizes a low conductivity wave absorbing material, meets the performance requirements of high-frequency information communication for wave absorbing materials, and has the advantages of good economicality, suitable for large-scale production, excellent wave absorbing performance and wide application frequency band.
Smart Images

Figure CN119763972A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal soft magnetic materials, and in particular to an iron-based amorphous alloy magnetic powder, a composite wave-absorbing coating prepared therefrom, and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, electromagnetic interference and electromagnetic radiation between various high-frequency electronic components have gradually become a problem that cannot be ignored. Electromagnetic interference and electromagnetic radiation not only affect the normal propagation and transmission of communication signals, but also pose a threat to human health. Therefore, how to eliminate and reduce electromagnetic interference and electromagnetic radiation has become an urgent problem to be solved in current information communication.
[0003] Absorbing materials are one of the most effective ways to eliminate electromagnetic interference and protect against electromagnetic radiation. Absorbing materials can absorb most of the electromagnetic waves projected onto their surface and dissipate them as heat. They are widely used in aerospace, radar, 5G communications, and medical fields. Soft magnetic metal alloys, as typical magnetic loss-type absorbing materials, have the characteristics of high saturation flux density, high economy, and stability, and have attracted much attention in the field of preparing absorbing materials.
[0004] At present, typical soft magnetic metal alloys include FeSiAl, FeCo, FeSi, FeNi and Fe-based amorphous / nanocrystalline. In order to maximize the entry of electromagnetic waves into the absorbing coating and dissipate them by converting them into heat through electromagnetic loss, the magnetic permeability of the absorbing coating must be equal to the dielectric constant to meet the impedance matching conditions. For traditional iron silicon aluminum alloy absorbing coatings, due to their high conductivity, their dielectric constant is much larger than the magnetic permeability, resulting in impedance mismatch and deterioration of the absorbing effect. Therefore, it is necessary to find materials with low conductivity to meet the performance requirements of high-frequency information communication for absorbing materials. Iron-based amorphous materials have the characteristics of long-range disorder and short-range order in the microstructure. Due to the disordered arrangement of atoms and the lack of crystal anisotropy, they have the characteristics of high magnetic permeability, high resistivity and low loss, and are regarded as a new generation of "green" soft magnetic materials.
[0005] However, the existing Fe-based amorphous materials often need to use expensive metal materials such as Nb and W, such as CN114045435A, CN113106358A, etc., which are poor in economy and industrial applicability; although CN112877615A avoids the use of expensive metal elements, the patent uses a melt quenching method to prepare amorphous nanocrystalline strips with high saturation magnetic flux density, but is not used for absorbing materials. CN114045435A needs to use precious metal elements such as W, Nb, and Mo, and its preparation method is to precipitate nanophases through heat treatment, and the microstructure is a mixture of amorphous nanocrystalline. CN113106358A directly uses spherical atomized powder to prepare absorbing materials, and also needs to use the precious metal Nb element. Summary of the invention
[0006] One of the purposes of the present invention is to provide an iron-based amorphous alloy magnetic powder to solve the above-mentioned problems.
[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: an iron-based amorphous alloy magnetic powder, the chemical composition of the iron-based amorphous alloy magnetic powder is: silicon content 5 at.%, boron content 7.5 at.%, phosphorus content 7-9 at.%, carbon content 2 at.%, chromium content 2 at.%, and the remainder is iron.
[0008] Among them, the main functions of boron, phosphorus and carbon elements are to improve the amorphous forming ability of iron-based amorphous alloys, so that they can meet the cooling rate requirements of amorphous powder prepared by water-gas combined atomization; the role of chromium element is mainly to further increase the mixing entropy and amorphous forming ability of iron-based alloys, while improving the corrosion resistance of the powder.
[0009] That is, the chemical formula of the iron-based amorphous alloy magnetic powder is Fe (74.5+x) 5B 7.5 P (9-x) C2Cr2, where X=0-2.
[0010] The second object of the present invention is to provide a method for preparing the above-mentioned iron-based amorphous alloy magnetic powder, the technical scheme adopted is to first prepare iron-based amorphous spherical powder by water-gas combined atomization method, and then flaked the spherical powder by ball milling to obtain ultrafine flaky iron-based amorphous alloy magnetic powder with a particle size D50 less than 40 μm. Among them, the finer powder particle size can reduce eddy current loss and improve high-frequency magnetic permeability.
[0011] The magnetic permeability of soft magnetic alloys is related to their Snoek limit. The Snoek formula reflects the relationship between the cutoff frequency and the product of the magnetic permeability of soft magnetic materials. The higher the initial magnetic permeability, the lower the cutoff frequency. Thinning and flattening magnetic powders can help break through the Snoek limit, thereby significantly improving the high-frequency magnetic permeability of soft magnetic alloys.
[0012] Compared with spherical magnetic powder, the flaky magnetic powder of the present invention has higher magnetic permeability and cutoff frequency, and can significantly improve its electromagnetic wave absorption performance. The spherical iron-based amorphous alloy powder is flattened and flaked by ball milling process to prepare ultrafine flaky iron-based amorphous alloy magnetic powder.
[0013] As a preferred technical solution, the water-gas combined atomization method includes the following steps: weighing industrial pure iron and placing it in a container, starting to apply induction heating, and after the pure iron is melted, adding silicon blocks, ferroboron, ferrophosphorus, metallic chromium and carbon sheets; melting all materials, and starting atomization after the molten pool temperature rises to 1450-1600°C; after the water-gas combined atomization is completed, the obtained iron-based amorphous powder is centrifugally dehydrated, blown dried, and sieved to obtain an iron-based amorphous spherical powder.
[0014] As a preferred technical solution, the water pressure during atomization is 80 MPa and the protective air pressure is 0.8 MPa.
[0015] As a preferred technical solution, the ball milling method is as follows: the ball milling speed is 300-500 r / min, the ball milling time is 10-12 h, the ball-to-material ratio is 20-25:1, ethanol is used as the ball milling medium, and zirconium dioxide microspheres are used as ball milling beads; the magnetic powder after ball milling is subjected to stress relief annealing at 460-480°C to obtain ultrafine flaky iron-based amorphous alloy magnetic powder.
[0016] The third object of the present invention is to provide a composite absorbing coating made of the above-mentioned iron-based amorphous alloy magnetic powder, and the technical solution adopted is that it also includes Sendust aluminum alloy powder, wherein the iron-based amorphous alloy magnetic powder accounts for 30wt.%-70 wt.%, and the balance is the Sendust aluminum alloy powder.
[0017] The purpose of the present invention is to adjust the magnetic permeability and high-frequency characteristics by adjusting the ratio of amorphous magnetic powder and sendust to meet different wave absorption requirements in low, medium and high frequency bands.
[0018] The present invention changes the ratio of ultrafine flaky iron-based amorphous alloy to iron-silicon-aluminum alloy powder, thereby regulating the electromagnetic parameters of the composite absorbing coating, so that the two materials cooperate with each other to obtain an absorbing material with good matching, excellent absorbing performance, light weight and wide application frequency band.
[0019] As a preferred technical solution, the chemical composition of the Sendust alloy is 9.6 at.%, 5.4 at.% aluminum, and the remainder is iron; the particle size D50 of the Sendust magnetic powder is greater than 100 μm. The Sendust magnetic powder is preferably flaky Sendust magnetic powder.
[0020] The fourth object of the present invention is to provide a method for preparing the above-mentioned composite absorbing coating, the technical scheme adopted is that the ultrafine flaky iron-based amorphous alloy and Sendust aluminum alloy powder are mixed with water-based polyurethane resin, deionized water and alcohol, stirred evenly, coated on a plastic film, and then dried to obtain the composite absorbing coating.
[0021] A fourth object of the present invention is to provide an application of the composite absorbing coating prepared by the above method, wherein the composite absorbing coating is adhered to a metal surface to eliminate or reduce electromagnetic radiation.
[0022] Since a single soft magnetic metal absorbing coating is difficult to simultaneously meet the shielding requirements of electromagnetic waves in the low, medium and high frequency ranges, the compounding of multiple soft magnetic alloys is beneficial to broaden the frequency band of absorbing materials and construct absorbing coatings in different applicable bands.
[0023] Compared with the prior art, the advantages of the present invention are: the iron-based amorphous alloy of the present invention does not contain precious metals such as Nb and W, has good economy and is suitable for large-scale production; ultrafine flaky iron-based amorphous alloy magnetic powder and traditional iron-silicon-aluminum alloy powder are mixed in a certain proportion, and the obtained iron-based amorphous composite magnetic metal micropowder absorbing coating has the advantages of adjustable electromagnetic parameters, excellent absorbing performance and wide application frequency band. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD spectrum of the spherical soft magnetic powder prepared in Example 1; Figure 2 This is the SEM spectrum of the spherical soft magnetic powder prepared in Example 1; Figure 3 This is the SEM spectrum of the ultrafine flaky Fe-based amorphous alloy magnetic powder prepared in Example 1; Figure 4 The iron-based amorphous composite magnetic metal powder absorbing coating prepared in Example 1; Figure 5 This is the magnetic spectrum of the iron-based amorphous composite magnetic metal powder absorbing coating prepared in Example 1. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the accompanying drawings.
[0026] Embodiment 1:
[0027] A composite radar absorbing coating, the preparation method of which comprises the following steps: (1) Preparation of ultrafine flaky iron-based amorphous alloy magnetic powder: 1) Use industrial pure iron, silicon block, ferroboron, metallic chromium and carbon sheet to prepare the raw materials of iron-based amorphous alloy for induction melting. The chemical composition of the iron-based amorphous alloy is: silicon content 5 at.%, boron content 7.5 at.%, phosphorus content 9 at.%, carbon content 2 at.%, chromium content 2 at.%, and the balance is iron; accurately weigh; 2) First, industrial pure iron is placed in a crucible and induction heating is started; after the pure iron is melted, silicon blocks, ferroboron, ferrophosphorus, metallic chromium and carbon sheets are added in sequence; after all materials are melted, the slag is removed after standing for 3 minutes; after the molten pool temperature rises to 1500°C, it is inverted in a tundish crucible and atomized at a water pressure of 80MPa and a protective gas pressure of 0.8MPa; after the water-gas combined atomization is completed, the obtained iron-based amorphous powder is centrifugally dehydrated, air-dried, and passed through a 400-mesh sieve to obtain an iron-based amorphous spherical soft magnetic powder; its XRD spectrum and SEM spectrum are shown as follows: Figure 1 and Figure 2 As shown in the figure, it can be seen that the iron-based amorphous spherical soft magnetic powder prepared by the method has good sphericity and concentrated particle size distribution; 3) Then, a planetary ball mill was used to mill the flaky iron-based amorphous alloy magnetic powder. The specific method was as follows: the ball milling speed was 300 r / min, the ball milling time was 10 h, the ball-to-material ratio was 25:1, ethanol was used as the ball milling medium, zirconium dioxide microspheres were used as ball milling beads, and the abrasive was the iron-based amorphous powder prepared by the water-gas combined atomization process. The magnetic powder after ball milling was stress-relieved and annealed at 480°C to obtain ultrafine flaky iron-based amorphous alloy magnetic powder. The SEM spectrum of the prepared ultrafine flaky iron-based amorphous alloy magnetic powder is shown in the figure. Figure 3 As shown, from Figure 3 It can be seen that the iron-based amorphous alloy magnetic powder with flake shape and large diameter-to-thickness ratio can be prepared by ball milling process; 4) The ultrafine flaky iron-based amorphous alloy prepared in step 3) is combined with the iron-silicon-aluminum alloy to prepare an iron-based amorphous composite magnetic metal micropowder absorbing coating. The specific preparation method comprises the following steps: a total of 10g of ultrafine flaky iron-based amorphous alloy and iron-silicon-aluminum alloy powders are mixed and stirred evenly with 8g of waterborne polyurethane resin, 6g of deionized water, and 20g of alcohol, and then coated on a plastic film, and then dried at 90°C for 2h to prepare an iron-based amorphous composite magnetic metal micropowder absorbing coating; a macroscopic photograph of the prepared iron-based amorphous composite magnetic metal micropowder absorbing coating is shown in FIG. Figure 4 As shown, it can be known that the process of the present invention can be used to prepare a wave-absorbing coating with uniform structure and flatness; the composition ratio of the ultrafine flaky iron-based amorphous alloy and the sendust aluminum alloy is 70 wt.% of the ultrafine flaky iron-based amorphous alloy, and the remainder is the sendust aluminum alloy powder; the chemical composition of the sendust aluminum alloy is 9.6 at.%, the aluminum content is 5.4 at.%, and the remainder is iron; the particle size D50 of the sendust aluminum magnetic powder is greater than 100 μm, and it comes from Mianyang Xici Technology Co., Ltd.; 5) Using Agilent 8363 vector network analyzer, measure the magnetic spectrum of the iron-based amorphous composite magnetic metal powder absorbing coating prepared in step 4) in the range of 0.1 to 1 GHz. The results are as follows: Figure 5 As shown, from Figure 5 It can be seen that the microwave absorbing coating prepared by the present invention has the characteristics of good high-frequency stability; It can be seen from Example 1 that the method for preparing an iron-based amorphous composite magnetic metal powder absorbing coating provided by the present invention can provide an absorbing coating with good frequency stability, which can lay a solid foundation for further application.
[0028] Embodiment 2:
[0029] Compared with the above-mentioned embodiment 1, the present embodiment is different in that: In step (1) 1), the chemical composition of the iron-based amorphous alloy is: silicon content 5 at.%, boron content 7.5 at.%, phosphorus content 7 at.%, carbon content 2 at.%, chromium content 2 at.%, and the balance is iron; In step (1) 3), the ball milling time is 12 h; In step (4), the composition ratio of the ultrafine flaky iron-based amorphous alloy and the Sendust aluminum alloy is 30 wt.% of the ultrafine flaky iron-based amorphous alloy, and the remainder is Sendust aluminum alloy powder; The rest is the same as in Example 1; The absorbing coating prepared in this embodiment 2 has a higher magnetic permeability in the low frequency band (less than 10M), which can meet the anti-radiation and interference requirements of electromagnetic waves in the low frequency band.
[0030] The present invention can further adjust the electromagnetic properties in the low-frequency, medium-frequency and high-frequency ranges by adjusting the ratio of Fe-based non-crystalline magnetic powder and flaky sendust magnetic powder, which is beneficial to broadening the use frequency band of absorbing materials and constructing absorbing coatings in different applicable bands.
[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An iron-based amorphous alloy magnetic powder, characterized in that: The chemical composition of the iron-based amorphous alloy magnetic powder is: silicon content 5 at.%, boron content 7.5 at.%, phosphorus content 7-9 at.%, carbon content 2 at.%, chromium content 2 at.%, and the balance is iron.
2. The method for preparing the iron-based amorphous alloy magnetic powder according to claim 1, characterized in that: Firstly, a water-gas combined atomization method is used to prepare an iron-based amorphous spherical powder, and then the spherical powder is flaked by ball milling to obtain an ultrafine flaky iron-based amorphous alloy magnetic powder with a particle size D50 less than 40 μm.
3. The preparation method according to claim 2, characterized in that: The water-gas combined atomization method comprises the following steps: weighing industrial pure iron and placing it in a container, starting to apply electricity for induction heating, and after the pure iron is melted, adding silicon blocks, ferroboron, ferrophosphorus, metal chromium and carbon sheets; melting all materials, and after the temperature of the molten pool rises to 1450-1600° C., starting atomization; after the water-gas combined atomization is completed, centrifugally dehydrating the obtained iron-based amorphous powder, drying it with air blast, and passing it through a sieve to obtain an iron-based amorphous spherical powder.
4. The preparation method according to claim 2, characterized in that: The water pressure during atomization is 80MPa and the protective air pressure is 0.8MPa.
5. The preparation method according to claim 2, characterized in that: The ball milling method comprises the following steps: the ball milling speed is 300 to 500 r / min, the ball milling time is 10 to 12 h, the ball-to-material ratio is 20 to 25:1, ethanol is used as the ball milling medium, and zirconium dioxide microspheres are used as the ball milling beads; and the magnetic powder after ball milling is subjected to stress relief annealing at 460 to 480° C. to obtain ultrafine flaky iron-based amorphous alloy magnetic powder.
6. A composite microwave absorbing coating made from the iron-based amorphous alloy magnetic powder of claim 1, characterized in that: It also includes Sendust aluminum alloy powder, wherein the iron-based amorphous alloy magnetic powder accounts for 30 wt.% to 70 wt.%, and the balance is the Sendust aluminum alloy powder.
7. The composite radar absorbing coating according to claim 6, characterized in that: The chemical composition of the sheet-shaped Sendust alloy is 9.6 at.%, 5.4 at.% aluminum and the remainder is iron; the particle size D50 of the Sendust magnetic powder is greater than 100 μm.
8. The method for preparing the composite radar absorbing coating according to claim 6, characterized in that: The ultrafine flaky iron-based amorphous alloy and Sendust aluminum alloy powder are mixed with waterborne polyurethane resin, deionized water and alcohol, stirred evenly, coated on a plastic film, and then dried to obtain the product.
9. Application of the composite radar absorbing coating prepared by the method according to claim 8, characterized in that: The composite absorbing coating is pasted on a metal surface to eliminate or reduce electromagnetic radiation.
Citation Information
Patent Citations
High-magnetic-induction iron-based amorphous soft magnetic alloy and preparation method thereof
CN112877615A
Iron-based amorphous alloy / graphene wave-absorbing material and preparation method thereof
CN113106358A
Iron-based amorphous nanocrystalline wave-absorbing material and preparation method thereof
CN114045435A